KEBUTUHAN PERAWATAN PERIODONTAL PADA PASIEN OBESITAS DI LINGKUNGAN RSGM FKG UNPAD - Aldilla Miranda; Nunung Rusminah; Prajna Metta (Journal of Syiah Kuala Dentistry Society, 2017)
Body Mass Index (BMI) is very related to various periodontal index such as attachment loss, pocket depth, gingival bleeding and calculus index according to a survey conducted in the United States (the third National Health and Nutrition Examination Survey/NHANES III). This study aimed to determine the Periodontal Treatment Needs of obese patients in FKG RSGM UNPAD. This kind of research is descriptive survey method, obtained a total of 15 obese subjects according to the criteria of BMI (Body Mass Index). Then performed plaque assessment using plaque index of Silness and Loe, and assesment of Community Periodontal Index Treatment Needs (CPITN). The results showed that for the CPITN, 60% of the sample experienced bleeding gums (bleeding), CPITN score 1 and 40% of the sample experienced bleeding and calculus there, CPITN score 2. Conclusions, the results showed all of obese patients in FKG RSGM UNPAD, need OHI, and more than half need scaling and prophylaxis as periodontal treatments.Keyword: Obesity, Periodontal Disease, CPITN